The complete chloroplast genome of Glehnia littoralis, an Endangered medicinal herb of Apiaceae family - Zhou, Yifeng (Mitochondrial DNA B Resour, 2018)
Glehnia littoralis is an important medicinal herb disjunctly distributed at sandy beaches in eastern Asia and western North America. The complete chloroplast genome sequence of G. littoralis is 147,552 bp in length and structurally divided into four distinct regions: two copies of inverted repeat of 18,365 bp separated by a large single copy (LSC) of 93,277 bp and a small single copy (SSC) of 17,545 bp. A total of 129 genes are annotated including 85 protein-coding genes, 36 tRNA gene, and eight rRNA genes. Phylogenetic relationship revealed that G. littoralis is closely related to Angelica dahurica in Apiaceae.